2019
DOI: 10.1002/ar.24199
|View full text |Cite
|
Sign up to set email alerts
|

A Problematic Tyrannosaurid (Dinosauria: Theropoda) Skeleton and Its Implications for Tyrannosaurid Diversity in the Horseshoe Canyon Formation (Upper Cretaceous) of Alberta

Abstract: Several published censuses have noted the presence of two tyrannosaurids, Daspletosaurus sp. and Albertosaurus sarcophagus, within the Upper Cretaceous Horseshoe Canyon Formation of Alberta. Although A. sarcophagus is known from more than a dozen major discoveries in these strata, Daspletosaurus sp. is known from just a single problematic skeleton (lacking most of the skull) of a young individual. Here we describe and figure this skeleton, and marshal a variety of osteohistologic, morphometric, and phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 54 publications
(149 reference statements)
1
29
0
Order By: Relevance
“…They concluded that although there is no clear evidence for the identity of the specimen, combined results strongly imply the taxonomic identification as young Albertosaurus sarcophagus . Although I agree with the presented results in Mallon et al (2020), minor parts of comparative descriptions provided by Mallon et al (2020) to support the affinity of the specimen as Albertosaurus require comments and corrections. The purpose of this submission is to discussing whether some of the characters that were used for the identification are taxonomically meaningful or not.…”
Section: Taxon Specimen Number Rostral Margin Of Dentary Position Of supporting
confidence: 87%
See 4 more Smart Citations
“…They concluded that although there is no clear evidence for the identity of the specimen, combined results strongly imply the taxonomic identification as young Albertosaurus sarcophagus . Although I agree with the presented results in Mallon et al (2020), minor parts of comparative descriptions provided by Mallon et al (2020) to support the affinity of the specimen as Albertosaurus require comments and corrections. The purpose of this submission is to discussing whether some of the characters that were used for the identification are taxonomically meaningful or not.…”
Section: Taxon Specimen Number Rostral Margin Of Dentary Position Of supporting
confidence: 87%
“…I read with interest the recent study by Mallon et al (2020) that re‐examined the articulated tyrannosaurid skeleton (CMN 11315) with controversial identity from Upper Cretaceous Horseshoe Canyon Formation of Alberta, which assigned to Albertosaurus sarcophagus by some authors (e.g., Holtz Jr., 2004), while classified as Daspletosaurus sp. by others (e.g., Russell, 1970).…”
Section: Taxon Specimen Number Rostral Margin Of Dentary Position Of mentioning
confidence: 99%
See 3 more Smart Citations